Implementasi Sistem Integrasi Layanan Deklarasi Keimigrasian All Indonesia di Tempat Pemeriksaan Imigrasi Bandara Ngurah Rai, Bali - Ida Bagus Yogi Pranaditha; Ni Putu Tirka Widanti; Ida Ayu Putu Sri Widnyani (ARRUS Journal of Engineering and Technology, 2026)
The objective of this study is to analyze the implementation of the All Indonesia Immigration Declaration Service Integration System at the Ngurah Rai Airport Immigration Checkpoint in Bali, to identify obstacles and challenges, and to formulate strategic and operational solutions. The impetus for this research stems from two key factors. Firstly, the number of international travelers has reached 15 million per year, exhibiting a 14% growth rate. Secondly, the fragmentation of health, customs, and immigration declaration systems has led to inefficiencies and security gaps in the past. The All Indonesia system, which has been fully operational since October 2025, integrates all declarations into a single digital platform with an H-3 arrival declaration feature. The present study employs a descriptive qualitative method with a case study approach. The data were collected through a variety of methods, including in-depth interviews with key informants from the Ngurah Rai Class I Special TPI Immigration Office, direct observation in the international arrival area, document review, and analysis of system submission data from October 2025 to January 2026. The data analysis employed the interactive model developed by Miles and Huberman, with Max Weber's Rational Bureaucracy theory serving as the analytical framework. The study's findings indicate that the system's implementation successfully reduced inspection times by 60–70 percent at manual counters and 80 percent at autogates. Furthermore, the system was adopted by 2.5 million passengers within four months. However, a number of technical challenges were identified, including system disruptions and recurring OCR errors, low pre-arrival data entry rates among Indonesian citizens (30–38 percent), suboptimal cross-agency data interoperability, and limited multilingual support. Solutions were formulated in the Adaptive Digital Bureaucracy Model, which encompasses the strengthening of a resilient system architecture, adaptive knowledge management, structured collaborative governance, user-centered design, and transformational change management.